2015
DOI: 10.1590/1413-81232015209.17322014
|View full text |Cite
|
Sign up to set email alerts
|

Classificação das perdas dentárias: fatores associados a uma nova medida em uma população de adultos

Abstract: Classificação das perdas dentárias: fatores associados a uma nova medida em uma população de adultosTooth loss classification: factors associated with a new classification in an adult population group 8,52 (± 9,24) (RP = 2,9); para perda acima de 13, a idade (RP = 1,3), classe social baixa (RP = 3,8); e ida ao dentista por emergência (PR = 9,4). Idade foi associada a perdas dentárias no presente estudo. A classificação permitiu diferenciar variáveis de acordo com a posição ou o número de dentes perdidos. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
0
8
0
12
Order By: Relevance
“…In spite of differences in the methodology of longitudinal tooth loss studies, such as the exclusion of third molars from analysis [11, 12], use of a restricted age group, between 35 and 44 years [22], as recommended by WHO, and number of years of follow-up, it was possible for the authors of the present study to verify a methodological pattern of higher incidence of tooth loss as the period of the follow-up increased [15, 16, 20] and the age group studied was older [24]. Moreover, even if most studies considered age an associated or risk factor of tooth loss [5, 18, 19, 25], this association is questionable, because there is no established evidence between tooth loss and the physiology of aging [24]. …”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In spite of differences in the methodology of longitudinal tooth loss studies, such as the exclusion of third molars from analysis [11, 12], use of a restricted age group, between 35 and 44 years [22], as recommended by WHO, and number of years of follow-up, it was possible for the authors of the present study to verify a methodological pattern of higher incidence of tooth loss as the period of the follow-up increased [15, 16, 20] and the age group studied was older [24]. Moreover, even if most studies considered age an associated or risk factor of tooth loss [5, 18, 19, 25], this association is questionable, because there is no established evidence between tooth loss and the physiology of aging [24]. …”
Section: Discussionmentioning
confidence: 66%
“…From this, we inferred a greater need for low complexity treatments that could have been made by primary oral health care in the initial stages of dental caries [17]. Most studies have, however, demonstrated the need for more dental services in secondary care for adults [9, 19], mostly due to the high accumulated demand [28]. This result becomes important since tooth loss is a direct consequence of lack of dental caries treatment.…”
Section: Discussionmentioning
confidence: 99%
“…- Model I: The cutoff point of 12 missing teeth was established, including the anterior arch, based on Batista et al ( 23 ). This model was designed considering the shortened dental arch concept, which considers that ten pairs of teeth that occlude, without presenting aesthetic spaces can be considered satisfactory.…”
Section: Methodsmentioning
confidence: 99%
“…This is the first prospective population-based cohort study on oral health in adults in Brazil, and the information from this cohort can be verified in recent publications, whether in respect to baseline (first-wave) [8, 11, 13, 2024] and second-wave data [12, 13, 18, 25].…”
Section: Discussionmentioning
confidence: 57%